2016
DOI: 10.1111/php.12566
|View full text |Cite
|
Sign up to set email alerts
|

Comparison ofUVProtection Properties of Cotton Fabrics Treated with Aqueous and Methanolic Extracts ofAchyranthes asperaandAlhagi maurorumPlants

Abstract: UV radiations are high-energy radiations present in sunlight that can damage human skin. Protection against these radiations becomes vital especially in those areas of the globe where UV index is quite high that makes the inhabitants more prone to dangerous effects of UV radiations. Clothing materials are good blockers of UV radiations, particularly when the fabric cover factor is high and/or the fabrics contain suitable UV-blocking finishes. In this study, effect of application of aqueous and methanolic extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In our previous work, we successfully achieved excellent UV protection on fabric by treating it with colorless plant extracts rich in flavonoids and phenolic contents . Current research is also a continuation of the same concept.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In our previous work, we successfully achieved excellent UV protection on fabric by treating it with colorless plant extracts rich in flavonoids and phenolic contents . Current research is also a continuation of the same concept.…”
Section: Introductionmentioning
confidence: 90%
“…In our previous work, we successfully achieved excellent UV protection on fabric by treating it with colorless plant extracts rich in flavonoids and phenolic contents. 41 Current research is also a continuation of the same concept. In this work, Amaranthus virdis and Solanum nigram were selected from 12 plants subjected to screening tests for identification of phenolic and flavonoid contents.…”
mentioning
confidence: 97%
“…The British Standards institute has also developed a standard for evaluating the photo-protection by children clothing. However, the standards developed for evaluation of UV protection of textiles mostly focus on Protection from UV radiation through clothing unstretched dry fabric, which is not the situation in practical wearing (Morison, 2003;Saleem et al, 2019;Nazir et al, 2016).…”
Section: Standard Testing Methodsmentioning
confidence: 99%
“…The chemical constituents of A. bidentata include oleanolic acid glycosides, saponins, ecdysterone, ketosteroids, and flavonoids [6]. Although modern pharmacological studies have shown that A.bidentata has a plethora of bio-activities, including anti-osteoarthritis [7], improving memory [8], regulating blood sugar level [9], preventing apoptosis [10], promoting angiogenesis, UV protection [11], anti-convulsion [12], anti-osteoporosis [13], improving xerophthalmia [14], and alleviating acute kidney injury [15], this herb is commonly used in the clinical treatment of osteoarthritis. After being salt-processed, the effects will be dramatically enhanced.…”
Section: Introductionmentioning
confidence: 99%